Changes of tissue images visualised by ultrasonography in the process of pressure ulcer occurrence. (1st April 2019) - Kitamura, Aya; Yoshimura, Mine; Nakagami, Gojiro; Yabunaka, Koichi; Sanada, Hiromi
Abstract : Objective: Ultrasonography is suitable for assessing pressure ulcers, and several features of ultrasonographic images that indicate abnormalities have been reported. However, no study has compared ultrasonographic images between normal and pressure-loaded skin and subcutaneous tissue from the same patients. This study aimed to assess lateral thoracic tissue using ultrasonography for both pre- and postoperative conditions and investigate changes in the tissue caused by loading. Surgeries were performed with patients in the park-bench position. Method: A nursing researcher obtained ultrasonographic images of the skin and subcutaneous tissue of the lower thoracic region in areas in contact with the surgical table one or two days before and after surgery. This study focused on three groups of two patients who had a category I pressure ulcer (PU), blanchable erythema, or normal skin on their lateral thoracic region. Results: A total of six patients participated. Postoperatively, muscle layers became thinner and less clear compared with pre-operative conditions in patients with the Category I pressure ulcers. These patients complained of significant pain in the areas of their pressure ulcers. Conclusion: Thickness of muscle layers could be an early sign of deep tissue injury.